2017
DOI: 10.18632/oncotarget.22024
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol overload in the liver aggravates oxidative stress-mediated DNA damage and accelerates hepatocarcinogenesis

Abstract: Primary liver cancers represent the second leading cause of cancer-related deaths worldwide. Diverse etiological factors include chronic viral hepatitis, aflatoxin and alcohol exposure as well as aberrant liver lipid overload. Cholesterol has been identified as a key inducer of metabolic impairment, oxidative stress and promoter of cellular dysfunction. The aim of this work was to address the oxidative stress-mediated DNA damage induced by cholesterol overload, and its role in the development of hepatocellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 47 publications
4
50
0
8
Order By: Relevance
“…Concordantly, cholesterol concentrations were elevated in human HCC [68]. Cholesterol increases oxidative stress and DNA damage, and thus contributes to HCC growth [69]. In the present study, cholesterol was higher in the tumors of all animals.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Concordantly, cholesterol concentrations were elevated in human HCC [68]. Cholesterol increases oxidative stress and DNA damage, and thus contributes to HCC growth [69]. In the present study, cholesterol was higher in the tumors of all animals.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, cholesterol was higher in the tumors of all animals. SREBP-2 is an important transcription factor enhancing cholesterol biosynthesis [69,70], but its active form was not changed in the tumors. ApoA1 protein was strongly diminished in the cancer tissues, and this illustrates that cholesterol accumulation may, in part, result from impaired reverse cholesterol transport [70].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol, as an essential component for lipid raft microdomains in the cellular membrane, is important for cancer growth and aggressiveness and for maintaining oncogenic growth signaling through the PI3K-AKT and STAT3 pathways [ 20 , 30 , 31 , 32 , 33 ]. Experimental or clinical evidence has previously shown that high levels of blood cholesterol accelerate hepatocarcinogenesis and lead to poor clinical outcomes in patients with HCC [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol, as an essential component for lipid raft microdomains in the cellular membrane, is important for cancer growth and aggressiveness and for maintaining oncogenic growth signaling through the PI3K-AKT and STAT3 pathways [ 20 , 30 , 31 , 32 , 33 ]. Experimental or clinical evidence has previously shown that high levels of blood cholesterol accelerate hepatocarcinogenesis and lead to poor clinical outcomes in patients with HCC [ 30 , 31 ]. Indeed, the anti-cancer and anti-metastatic effects of cholesterol-lowering drugs, such as simvastatin, lovastatin, and pitavastatin, which are mediated through suppression of the AKT and STAT3 pathways, have been shown in HCC, renal cancer, malignant melanoma, and ovarian cancer [ 22 , 23 , 24 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human manganese superoxide dismutase protein (rMnSOD) counteracts the progression of non‐alcoholic steatohepatitis (NASH) to HCC . Antioxidant N‐acetyl‐cysteine supplementation significantly prevents DNA oxidative damage from cholesterol overload in HCC tumorigenesis . Cancer stem cells (CSCs) are the crucial subpopulation of cancer cells that determine tumor initiation, self‐renewal, and heterogeneity.…”
Section: Introductionmentioning
confidence: 99%